Sustainable Tourism Beyond BAU (Brundtlund as Usual): Shifting From Paradoxical to Relational Thinking? - Hall CM (Frontiers Media S.A., 2022)
Tourism is a major economic activity and employment generator. According to the World Travel Tourism Council (2021), prior to the COVID-19 pandemic travel and tourism was an eight trillion-dollar industry that generated about 10 percent of the global GDP in 2019. Although global tourism was greatly affected by the COVID-19 pandemic, the loss of national and regional income as a result of the pandemic related mobility restrictions and resultant job loss, arguably have almost had a paradoxical effect in that tourism and hospitality has achieved greater public policy recognition because the impacts of COVID-19 have demonstrated just how economically important the tourism sector is.
Keywords: sustainable tourism; global change; tourist behavior; urban tourism; nature-based tourism; tourism system; tourism impacts; crisis